Physiologically‐Regulated Adhesion of Hydrogels for Wound Dressing. Issue 20 (27th September 2021) - Xu, Mengda; Miao, Yan; Yu, Jiahui; Zhang, Lidong
Abstract: Adhesion allows the close contact of wound dressing materials with skin surface. However, the dressing replacement inevitably causes the secondary damage to unhealed wound, so a wound dressing material having physiologically‐regulated adhesion is of high significance. Herein, a hydrogel is reported by covalently introducing cationic moieties into an elastic network. The cationic moieties are capable of electron‐withdrawing that promotes a strong electrostatic interaction with polar groups of protein (high electron cloud density) from the wound skin tissue, enabling the adhesion of hydrogel on the skin surface. With the tissue metabolism, the nucleophilic skin surface forms a lipid layer that gradually destroys the electrostatic interaction and weakens the interfacial affinity. The adhesion energy can be reduced from 60 to <10 J m −2 in 7 days, so that the dressing material can be removed easily. The cationic moieties also endow the hydrogel a high water swelling ratio (reaching 25 200%) and an efficient antibacterial property. The in vivo tests demonstrate that the wound on a mouse back reaches physiological 100% healing after the hydrogel dressing treatment for 12 days. All results show that the introduction of cationic moieties makes the hydrogel more promising as a wound dressing. Abstract : A cationic hydrogel with physiologically‐regulated adhesion on skin surface is reported, which as a wound dressing material can avert the secondary damage to patients caused by the dressing replacement. The high swelling ratio of 25 200% and antibacterial effects accelerate the wound healing. The in vivo tests demonstrate that the cationic moieties make the hydrogel more promising as a wound dressing.